A releitura cognitivo-semântica de Robert Hanna das formas de intuição de Kant: sobre o significado representacional do conteúdo não-conceitual no debate contemporâneo - Magalhães, Bergkamp Pereira (2020)
The present thesis proposes to investigate the debate regarding the possibility of existence and representational significance of non-conceptual content. For this, we will approach the interpretation of the non-conceptualist spectrum of the debate that defends this possibility against the most influential version of conceptualism, namely, John McDowell's conceptualism. In the first moment, we will show the importance of Gareth Evans and John McDowell for the contemporary debate, since the first is responsible for introducing the notion of non-conceptual content in the contemporary debate and the second for the introduction of the so-called demonstrative concepts to defend the conceptualist spectrum. In addition, we will show two positions regarding the non-conceptual notion of Evans's writings in relation to demonstrative concepts in order to understand the importance of non-conceptual content to be taken as representation. The perspective of Robert Stalnaker, who stands in favor of the state view, and Richard Heck who stands in favor of the content view. The objective is to point out the main issues within the contemporary debate to understand the purposes of Robert Hanna's argument exposed in the second part. In the second moment, we will present two perspectives of interpretation of Kant's writings. Hanna's non-conceptualist semantic-cognitive rereading and John McDowell's conceptualist epistemic-metaphysical reading that understands that Kant is the precursor of conceptualism. The objective is to elucidate how the so-called “forms of intuition” constitutively explain the non-conceptual content and how this constitutive role is played in the non-conceptual content from the Argument from Incongruent Counterparts. Finally, we will trace the relationship between Hanna's cognitive-semantic reinterpretation proposal of Kant's writings and the non-conceptualist spectrum of contemporary debate to indicate how these writings offer answers to the problems faced by the non-conceptualist spectrum of the current debate.